Putative ergothioneine transporter of salmonids as a functional tool for ergothioneine supplementation - Kitsanayanyong, Lalitphan; Ishikawa, Yuki; Ohshima, Toshiaki (Aquaculture, 2022)
Ergothioneine transporter (ETT) plays an important role in the incorporation of dietary ergothioneine (ET), a potent hydrophilic antioxidant produced intensively in certain edible mushroom species, in living organisms. We recently characterized ETT in rainbow trout (Oncorhynchus mykiss). However, the investigation of ETT in other commercially important salmonids is lacking. The present study aimed to provide molecular information on putative ETTs in coho salmon (Oncorhynchus kisutch), Atlantic salmon (Salmo salar), and chinook salmon (Oncorhynchus tshawytscha), particularly bioinformatic identification, gene expression in blood cells, muscle, intestine, and liver, which is responsible for deposition of ET in muscle, and development of universal primer set for quantitative real-time polymerase chain reaction (qPCR). In addition, ET concentration in these salmonids was investigated. The high sequence identity of putative ETT genes (E1s) to the characterized ETT orthologs and their placement under the ETT clade in the phylogenetic tree indicated that E1s are the putative ETTs of salmonids. The relationship between putative ETT gene expression ratio and the corresponding ET concentrations in the blood cells (whole blood for ET concentration), liver, intestine, and muscle suggested that the putative ETTs should act as ETTs. Species-specific primer sets and a universal primer set applicable for qPCR of these salmonid species were successfully developed and used for quantitative gene expression analysis. The present study successfully provides genomic information on the putative ETTs, and a universal primer set that is advantageous for detecting the expression of putative ETT genes in edible fish species. The expression of putative ETT genes highlights the potential of ET supplementation in future aquaculture of salmonids as a strategy to prevent quality deterioration due to lipid oxidation and discoloration of their flesh during storage. 公開予定日: 2023-09-23 19K06235 journal article